Disentangling fathers' absences from household remittances in international migration The case of educational attainment in Guatemala - Davis, Jason (International journal of educational development, 2016)
Estimating the effects of international migration on left-behind children's educational attainment is complicated by the potential offsetting effects of fathers' absences and household remittances. Most research has not separated these aspects of international migration on children's human capital outcomes. We address this deficiency by using instrumental variables to isolate the effects of fathers' international migration absences from international household remittances on student enrollment and grade progression in Guatemala. Results indicate that fathers' absences and household international remittances are negatively related to enrollment, providing evidence for a culture of migration effect. For students who remain in school, household international remittances neutralize the harmful influence of fathers' absences on grade progression